Repeat Surgery following Temporal Inverted ILM Flap Technique: Next Step after Primary Failure - Alagoz, Cengiz; Bektasoglu, Damla; Alagoz, Nese; Erdogdu, Erdem; Artunay, Özgür (Klinische Monatsblätter für Augenheilkunde, 2023)
Purpose We aimed to report our surgical experience with repeat surgery as the next step after an unsuccessful hole closure with the primary single-layered temporal inverted flap technique (IFT).Methods We identified cases with persistent macular holes by reviewing the records of eyes that underwent IFT between October 2018 and October 2021. These cases were evaluated for hole features, anatomical closure, and visual improvement before and after the first and second surgeries. In addition, the technique applied in repeat surgery was recorded. Optical coherence tomography (OCT) images at follow-up were used to evaluate the flap position.Results A persistent hole was identified in 11 (6.4%) of 172 patients who underwent IFT. An inferotemporal displacement was observed in seven eyes, while no flap could be identified in the OCT images of the other four eyes. In the second surgery, the old flap was reinverted in one eye, and a new flap was created from the superior region in five eyes and the nasal region in the other five eyes and was stabilized under perfluorocarbon liquid. A gas tamponade (C3F8/SF6) was used in all patients at the end of surgery. The minimum hole diameter was > 400 µm in all eyes and 100% closure was achieved after the second surgery. Visual acuity gain of ≥ 3 lines was observed in 9 of the 11 eyes (81.8%). The mean visual acuity increase at the last follow-up was significant (p = 0.008).Conclusion With single-layer temporal IFT in the primary surgery of macular holes, unsuccessful results may be observed due to the flap displacement in the early period. In our series, IFT was applied again with the use of the old flap or the creation of a new flap in the second surgery of the persistent holes, and successful results were obtained.
Keywords: inverted flap technique; persistent macular hole; repeat surgery